(untitled) (Journal of humanities and social sciences exploratio, 2026)
The Farewell Waltz, written by Milan Kundera, mainly contains three clues, in which the main characters are connected through an ingenious design and exaggerated coincidences, making this novel a skillfully constructed masterpiece. In light of ethical literary criticism, this essay attempts at analyzing the ethnic environment, ethnic selection and ethnic identity of the main characters according to the three clues, which can not only help us understand the ethics raised by Kundera, but also provide us with insightful advice for establishing a correct ethnic value.